Description of Paenibacillus tepidiphilus sp. nov., isolated from a tepid spring. Issue 3 (27th January 2020) - Narsing Rao, Manik Prabhu; Dong, Zhou-Yan; Kan, Yu; Dong, Lei; Li, Shuai; Xiao, Min; Kang, Ying Qian; Zhang, Kun; Li, Wen-Jun
Abstract : China is a hotspot for hot springs and during microbial diversity analysis of Tengchong hot spring, Yunnan province, south-west PR China, two strains designated SYSU G01001 T and SY-13 were isolated. SYSU G01001 T and SY-13 were Gram-stain-positive, motile and spore-forming. Colonies were white, circular, raised and punctiform. SYSU G01001 T and SY-13 grew at pH 6.0–9.0 (optimum pH 8.0) and at 23–37 °C (optimum 28 °C). The 16S rRNA gene sequence similarity between SYSU G01001 T and SY-13 was 99.6 % but these strains shared low sequence similarity with Paenibacillus azotifigens (97.5 %) indicating that they represented a novel species. On the basis of the results, SYSU G01001 T was selected for further investigations and SY-13 was considered to represent a second strain of the species. The cell wall peptidoglycan of SYSU G01001 T was meso -2, 6-diaminopimelic acid and MK-7 was the only respiratory quinone. The polar lipids were diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), phosphatidylethanolamine (PE), two unidentified aminolipids (AL), two unidentified amino phospholipids (APL), an unidentified phospholipid (PL) and an unidentified polar lipid (L). The G+C content of the genomic DNA was 53.9 mol%. The average nucleotide identity (ANIb and ANIm) values between SYSU G01001 T and Paenibacillus azotifigens LMG 29963 T were below the cut-off level (95–96 %) recommended as the average nucleotide identity (ANI) criterion for interspecies identity. On the basis of the above results strain SYSU G01001 T represents a novel species of the genus Paenibacillus, for which the name Paenibacillus tepidiphilus sp. nov. is proposed. The type strain is SYSU G01001 T (=KCTC 33952 T =CGMCC 1.13870 T ).